Analysis of Cyanolipids from Sapindaceae Seed Oils by Gas Chromatography–EI‐Mass Spectrometry. Issue 4 (19th February 2014) - Tava, Aldo; Avato, Pinarosa
Abstract: As a continuation of our investigation on unusual lipids, in the present work we describe a method based on GC–FID and GC–EI‐MS to analyze the molecular composition of intact cyanolipids (CL) from selected Sapindaceae plants. We applied our method to the study of CL of type I (1‐cyano‐2‐hydroxymethyl‐prop‐2‐en‐1‐ol‐diester) from Paullinia cupana var. sorbilis and Allophylus dregeanus and CL type III (1‐cyano‐2‐hydroxymethyl‐prop‐1‐en‐3‐ol‐diester) from A. natalensis and Nephelium lappaceum . Our analytical approach allowed us to obtain useful mass spectra to identify individual isomeric molecular species composing the CL mixtures and resulted in the very sensitive detection and identification of minor CL. Defined CL mass spectra resulted in suitable detection of these phytochemicals in complex plant oil mixtures containing acylglycerols. To the best of our knowledge GC–EI‐MS spectra of cyanolipids have never been reported before. Moreover, this study improved previous knowledge of the lipid chemistry of Sapindaceae plants.